Segregation into and Replication of Plasmid Deoxyribonucleic Acid in Chromosomeless Segregants of Escherichia coli - Inselburg, Joseph (1970)
The progeny cells of Escherichia coli strain P678-54, which normally do not contain deoxyribonucleic acid (DNA), were found to carry DNA when the parental cell carried colicin factor E1 (Col E1). The DNA found in the normally DNA-less segregants was shown to be Col E1 DNA, which is present primarily as a covalently closed circular molecule that can undergo more than one complete cycle of replication.